BIOACTIVITY OF STREPTOMYCES AGAINST COLISTIN RESISTANT K. PNEUMONIAE ISOLATED FROM DIFFERENT CLINICAL SAMPLES - Dalal S.AL-Rubaye; T. S. Al-Rubaye (The Iraqi Journal of Agricultural science)
This study was aimed to find a hopeful antibacterial product from Streptomyces spp. acts against colistin-resistant Klebsiella pneumoniae isolated from different clinical samples. Among 46 K. pneumoniae isolates, 4 (8.7%) isolates represented Colistin resistance using the disc diffusion method and minimum inhibitory concentration. Out of 20 soil samples collected from different gardens at Essaouira city, 18 Streptomyces spp. were isolated and identified. The bioactivity of each Streptomyces isolate was checked against antibiotic-resistant pneumococci. The result showed that only six isolates had high antibacterial activity, 3 isolates with moderate activity, 7 isolates with weak activity, and two with no activity. PCR and DNA sequencing of 16s rDNA was done for the highest active Streptomyces spp. isolate, the result showed 96% identity to Streptomyces azureus.